PENERAPAN COOPERATIVE PEER INSTRUCTION BERBASIS ETNOGASTRONOMI UNTUK MENINGKATKAN LOCAL KNOWLEADGE - Barkatin, Moriza Pamor; Susilowati, Susilowati; Pratiwi, Nensi; Kertiani , Putu; Nabilah, Mirna Qurrotun (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
This study aims to improve students' learning activities and cognitive learning outcomes, particularly related to local knowledge, in the subject of Basic Culinary Arts, specifically in the chapter Indonesian Food Processing, sub-chapter Javanese Dishes, through the implementation of the Cooperative Peer Instruction model integrated with ethnogastronomy. The research method used is Classroom Action Research (CAR). The subjects of this study were students of Class X-Culinary 2 at SMK YPM 2 Taman in the academic year 2024/2025. The instruments used included pre-tests and post-tests in each cycle, checklist-based observation sheets, and field notes. The data obtained were analyzed descriptively. Based on observations from Cycle I and Cycle II, there was an increase in the percentage of students' learning activities and cognitive learning outcomes. Respectively, the students' activity percentages were 59.03% and 70.48%, while the percentage of cognitive learning mastery was 62.5% and 78.125%. It can be concluded that the implementation of the Cooperative Peer Instruction model integrated with ethnogastronomy in the chapter Indonesian Food Processing, sub-chapter Javanese Dishes, in this study was able to improve students' learning activities and cognitive learning outcomes in the learning process.